Malays online news and public opinion: a study of issues during the Semenyih by-election - Mat Yakim, Muhamad; Abdul Manan, Kamaruzzaman; Mohamed, Shafizan (2019)
Media can play an important role in the public's voting decision. Despite that, it is unknown whether the issues highlight by media agenda counterpart the issues of the public. Semenyih by-elections resulted in a second victory for Barisan Nasional. The factor that made the election a very interesting one was that the new government which was covered by various issues such as the recent loss of Cameron Highlands, the effectiveness of the new government's Pakatan Harapan (PH) and the strength of Barisan Nasional-PAS cooperation gave a big challenge to PH government to face in the Semenyih by-election. The majority of the voters are Malays, thus this will determine the strength of support in Malay society after GE14. In Malaysia, Facebook is the most popular social media that been used in political communication. This paper investigates whether news online such as Facebook set the agenda for its readers. In response to the importance of social networking sites as sources of information, news media organizations have set up Facebook channels in which they publish news stories or links to articles. This allows for a wider news reach as well as audience participation. When audience members read and subsequently comment on news articles on Facebook, it becomes possible to identify public opinions and sentiments on the issues being covered. Content analysis was used to analyse 398 issues that been highlighted by two Malays online news facebook page namely Malaysiakini BM and Sinar Harian during Semenyih by-election. Moreover, a total of 691 public responds from the issues been sampled to investigate whether user comments mirror the issues and sentiments presented in the news articles. The findings showed that news sentiments and audience sentiments did not necessarily have a clear relationship.